The Minoan enigma : deciphering Linear A - Tan, Kimberly Miracle Wei Yan (2019)
This study seeks to provide scholars with a new analysis of Linear A, focusing on the reconstruction and recombination of new possible clusters of symbols, and not only through the use of existing clusters of symbols as shown through the graphics of Linear A tablets. The procedure involves comparative linguistics and crypto-linguistics, where a brute-force attack will first be used on the recreated possible combination of clusters, followed by the comparison of these newly-formed clusters with two existing writing systems of the Semitic and Indo-European language families. Previous studies have indeed attempted to use probable historical relations to link Linear A with another language, but have yet to apply new formations of Linear A clusters to the field of comparative linguistics. A notable finding is that more Linear A tablets, from the tablets investigated, have been postulated to have a greater context with Semitic words rather than with Indo-European words, indicating that Linear A might be leaning more towards Semitic than Indo-European. However, no definite conclusion has been obtained from this study as to what the underlying language of Linear A could be, due to insufficient corpus analysed. A possible school of thought this paper follows is the hypothesis that the language of Linear A might have involved more than one language (or language families). Future research can ponder over this possibility while conducting work on a larger quantity of corpus.